Cubism - Apollinaire, Guillaume, 1880-1918 (Art of century collection., 2010)
This volume presents Cubism, the 20th century avant-garde art movement, pioneered by Pablo Picasso and Georges Braque, that revolutionized European painting and sculpture, and inspired related movements in music, literature and architecture. In cubist visual artworks, objects are broken up, analyzed, and re-assembled in an abstracted form -- instead of depicting objects from one viewpoint, the artist depicts the subject from a multitude of viewpoints to represent the subject in a greater context. Often the surfaces intersect at seemingly random angles, removing a coherent sense of depth. The background and object planes interpenetrate one another to create the shallow ambiguous space, one of cubism's distinct characteristics. This work offers a new interpretation of modernity's crucial moment, and permits the reader to rediscover, through biographies of Cubist artists such as the aforementioned Picasso and Braque and Juan Gris and Robert Delaunay, the principal representatives of the movement.